64 517
Assignments Done
99,3%
Successfully Done
In September 2018

Answer to Question #14625 in Trigonometry for Danielle

Question #14625
simplify:
(x^4)^-3 * 2x^4
Expert's answer
(x^4)^-3 * 2x^4= 2x^4/{(x^4)^3}=2/{(x^4)}^2=2/(x^8)=2x^{-8}

Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be first!

Leave a comment

Ask Your question

Submit
Privacy policy Terms and Conditions